2022
DOI: 10.1101/2022.08.25.505320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extreme sensitivity of fitness to environmental conditions; lessons from #1BigBatch

Abstract: The phrase 'survival of the fittest' has become an iconic descriptor of how natural selection works. And yet, precisely measuring fitness, even for single-celled microbial populations growing in controlled laboratory conditions, remains a challenge. While numerous methods exist to perform these measurements, including recently developed methods utilizing DNA barcoding, all methods seem limited in their precision to differentiate strains with small fitness differences. This limit on precision is relevant in man… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…In the aforementioned design, most such events (those that occur in the bulk of the fragment, between the inline indices) generate "inadmissible" index combinations that can be easily identified and discarded. Using this approach, we found that ~5% of reads had inadmissible index combinations (Venkataram et al, 2021), but others have reported rates of up to 43% (Kinsler et al, 2022). Note that, while it is possible to include inline indices in the one-step PCR setup, their utility would be limited.…”
Section: Inline Indicesmentioning
confidence: 88%
See 3 more Smart Citations
“…In the aforementioned design, most such events (those that occur in the bulk of the fragment, between the inline indices) generate "inadmissible" index combinations that can be easily identified and discarded. Using this approach, we found that ~5% of reads had inadmissible index combinations (Venkataram et al, 2021), but others have reported rates of up to 43% (Kinsler et al, 2022). Note that, while it is possible to include inline indices in the one-step PCR setup, their utility would be limited.…”
Section: Inline Indicesmentioning
confidence: 88%
“…In this setup, sample information can be encoded by a combination of four indices (two Illumina and two inline). In principle, samples tagged with different inline indices during the first PCR can be pooled together for the second PCR, although we do not recommend this practice due to the possibility of template switching events (Kinsler et al, 2022) .…”
Section: Inline Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we were unable to see a significant increase in fitness using either test for a clone carrying the YhjY S21S putative compensatory mutation, despite this mutation occurring in an extremely convergent manner across five independently evolving populations. Such apparent discrepancies may stem from the noisiness of the measurements themselves but likely often stem from the complexity of relative fitness itself (24). Relative fitness is likely strongly dependent on context and is the result of a complex interplay of factors.…”
Section: Discussionmentioning
confidence: 99%